Pengembangan Gim Edukasi Pengenalan Jenis Anjing Ras Berbasis Android - Santoso, Rio (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
This study aims to develop an educational game to be a medium for introducing dog breeds based on Android and developed using the Unity game engine with a quiz-themed game model. Game Development Life Cycle(GDLC) is used as the method of developing this game with stages: initiation, pre-production, production, testing, beta and release. The final result of this research is an educational game entitled “Introduction to Dog Races” which can be played on Android devices. Based on the results of the user trial questionnaire on 13 respondents, 38,5% (5 people) stated “Agree”, 53,8% (7people) stated “Strongly Agree” that the respondents became more familiar with dog breeds after playing the educational game “Introduction to Dog Races” .